Discoscopic Findings of High Signal Intensity Zones on Magnetic Resonance Imaging of Lumbar Intervertebral Discs. (21st May 2014) - Sugiura, Kosuke; Tonogai, Ichiro; Matsuura, Tetsuya; Higashino, Kosaku; Sakai, Toshinori; Suzue, Naoto; Hamada, Daisuke; Goto, Tomohiro; Takata, Yoichiro; Nishisho, Toshihiko; Goda, Yuichiro; Sato, Ryosuke; et al.
Abstract : A 32-year-old man underwent radiofrequency thermal annuloplasty (TA) with percutaneous endoscopic discectomy (PED) under local anesthesia for chronic low back pain. His diagnosis was discogenic pain with a high signal intensity zone (HIZ) in the posterior corner of the L4-5 disc. Flexion pain was sporadic, and steroid injection was given twice for severe pain. After the third episode of strong pain, PED and TA were conducted. The discoscope was inserted into the posterior annulus and revealed a migrated white nucleus pulposus which was stained blue. Then, after moving the discoscope to the site of the HIZ, a migrated slightly red nucleus pulposus was found, suggesting inflammation and/or new vessels penetrating the mass. After removing the fragment, the HIZ site was ablated by TA. To our knowledge, this is the first report of the discoscopic findings of HIZ of the lumbar intervertebral disc.